Optimalisasi Promosi dan Pemasaran Kebaya Secara Digital Berbasis Web Melalui Teknik SEO dan Penggunaan Chatbot AI pada Butik XYZ - Ayuningsih, Ekatri; Husna, Asmaul; Meuzaki, Ryezi; Panggabean, Jan Kevin (JURNAL RISET KOMPUTER (JURIKOM), 2025)
This study aims to optimize the promotion and marketing of kebaya digitally by applying Search Engine Optimization (SEO) techniques and the use of AI Chatbot in a web-based application. The main problem faced by Butik Putri is the rapid development of digital technology that pushes kebaya entrepreneurs to adapt their promotional and marketing strategies online. The advancement of digital technology and intence business competition drives growth in Indonesia’s fashion Industry, especially kebaya products, thus making digital marketing crucial to reach a broader and modern market. Butik Putri is a brand engaged in kebaya fashion. Currently, Butik Putri experiences limitations in digital marketing, which a restricted to the WhatsApp platform and lacks optimal service responsiveness. The proposed solution is to develop a web-based application by implementing Search Engine Optimization (SEO) strategies and AI Chatbot. This study aims to design and build a promotional website a modern, responsive interface that supports customer interaction through the application of Tailwind CSS and AI Chatbot integration. Additionally, Search Engine Optimization (SEO) techniques are applied to improve website visibility on Search Engines. The research method uses a qualitative approach, involving the Software Development Life Cycle (SDLC) method with prototype and flowchart models. The results show that the implementation of a Tailwind CSS-based website with AI Chatbot features can increase the volume of kebaya sales through both digital platforms and physical stores, strengthen the brand, and enhance real-time responsiveness and interaction with website visitors by providing 24-hour interactive service